Microvascular Sex- and Age- Dependent Phosphodiesterase Expression - Wang, Jianjie; Kazmi, Murtaza M.; Huxley, Virginia H. (Frontiers in Aging, 2021)
Objectives: The cyclic nucleotide 2nd messengers, cAMP and cGMP, are pivotal regulators of vascular functions; their cellular levels are tightly controlled by the cyclic nucleotide hydrolases, phosphodiesterases (PDE). Biologic sex and age are recognized as independent factors impacting the mechanisms mediating both vascular health and dysfunction. This study focused on microvessels isolated from male and female rats before (juvenile) and after (adult) sexual maturity under resting conditions. We tested the hypothesis that sexual dimorphism in microvascular PDE expression would be absent in juvenile rats, but manifest in adult rats. Methods: Abdominal skeletal muscle arterioles and venules were isolated from age-matched juvenile and adult male and female rats under resting conditions. Transcripts of five PDE families (1-5) associated with coronary and vascular function with a total of ten genes were measured using TaqMan real-time RT-PCR and protein expression of microvessel PDE4 was assessed using immunoblotting and immunofluorescence. Results: Overall expression levels of PDE5A were highest while PDE3 levels were lowest among the five PDE families (p < 0.05) regardless of age or sex. Contrary to our hypothesis, in juveniles, sexual dimorphism in PDE expression was observed in 3 genes: arterioles (PDE1A, female > male) and venules (PDE1B and 3A, male > female). In adults, gene expression levels in males were higher than females for five genes in arterioles (PDE1C, 3A, 3B, 4B, 5A) and three genes (PDE3A, 3B, and 5A) in venules. Furthermore, age-related differences were observed in PDE1-5 (in males, adult>juvenile for most genes in arterioles; in females, adult>juvenile for arteriolar PDE3A; juvenile gene expression > adult for 2 genes in arterioles and 3 genes in venules). Immunoblotting and immunofluorescence analysis revealed protein expression of microvessel PDE4. Conclusions: This study revealed sexual dimorphism in both juvenile and adult rats, which is inconsistent with our hypothesis. The sex- and age-dependent differences in PDE expression implicate different modulations of cAMP and cGMP pathways for microvessels in health. The implication of these sex- and age-dependent differences, as well as the duration and microdomain of PDE1-5 activities in skeletal muscle microvessels, in both health and disease, require further investigation.